2015
DOI: 10.5430/jnep.v6n2p55
|View full text |Cite
|
Sign up to set email alerts
|

Community-based nursing education in South Africa: A grounded-middle range theory

Abstract: Background: The change to a democratically elected government in South Africa in 1994 brought with it an impetus for change in public health and education systems, which was signalled by a number of policy documents. Traditional content-driven education was to be replaced by a community-oriented approach to education. Community-based education was to be the vehicle through which health care students and health personnel educators would be equipped with the comprehensive knowledge, competencies and attitudes ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Health care reforms alter the environment in which nurses and other health care workers practice. The review found that in Sub Saharan Africa, emphasis on primary care, emerging of new health challenges, increasing burden of disease significantly demand need for curriculum reforms [ 21 23 ]. Mthembu et al [ 22 ] reported that reforms in curricula are necessary to ensure that nursing education produces graduates who influence the quality of the health care system and are relevant to the needs of the population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care reforms alter the environment in which nurses and other health care workers practice. The review found that in Sub Saharan Africa, emphasis on primary care, emerging of new health challenges, increasing burden of disease significantly demand need for curriculum reforms [ 21 23 ]. Mthembu et al [ 22 ] reported that reforms in curricula are necessary to ensure that nursing education produces graduates who influence the quality of the health care system and are relevant to the needs of the population.…”
Section: Resultsmentioning
confidence: 99%
“…Mtshali and Gwele [ 21 ] developed a middle range model that would guide the practice of community based education in basic nursing education in South Africa. This curriculum reform in nursing education reported community based education as relevant, responsive education and education for social justice that consciously and deliberately socialize health delivery towards primary health care.…”
Section: Resultsmentioning
confidence: 99%
“…(7)(8)(9) This study showed that although community-based training and internship along with professors have some challenges such as shortage of facilities, equipment, and human resources, it was evaluated as useful for the community by students and professors participated in this study. The results were in line with those of similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this systematic review indicate that community-based education promotes the development of professional skills in nursing students [11,19,20,22,24,27,31,32]. Research has shown that the use of community experiences in educational programs enhances professional skills [10]. Community-based education occupational competencies and skills such as problem-solving, leadership, and management [9].…”
Section: Discussionmentioning
confidence: 92%
“…Internationally, changes to education have taken place. For example, the South African government called for a shift in health care education from a traditional content-based approach to a community-based approach so that students and educators could experience it [10]. UK health policy has emphasized community-based care in recent years because it has been shown to increase nurses' competence and confidence [11].…”
Section: Introductionmentioning
confidence: 99%